2015
DOI: 10.1128/aac.00997-15
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal Activities of Novel Methylseleno-Imidocarbamates

Abstract: fThe generation of new antileishmanial drugs has become a priority. Selenium and its derivatives stand out as having promising leishmanicidal activity. In fact, some parasites express selenoproteins and metabolize selenium. Recently, selenium derivatives have shown the potential to reduce parasitemia, clinical manifestations, and mortality in parasite-infected mice. In this paper, after selecting four candidates according to drug similarity parameters, we observed that two of them, called compounds 2b [methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…In the last decade, anticancer drugs have been explored as candidates against infectious pathologies (9,20,21). Recently, several small molecules containing the Se atom have been reported as leishmanicidal agents (7). Here, we evaluated antileishmanial potential of some recently reported sulfur and selenium compounds bearing isothio-/isoselenocyanate and thio-/selenourea moieties attached to a naphthalimide or a phenylalkyl skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, anticancer drugs have been explored as candidates against infectious pathologies (9,20,21). Recently, several small molecules containing the Se atom have been reported as leishmanicidal agents (7). Here, we evaluated antileishmanial potential of some recently reported sulfur and selenium compounds bearing isothio-/isoselenocyanate and thio-/selenourea moieties attached to a naphthalimide or a phenylalkyl skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Karelia et al analyzed selenium derivatives of these naphthalimide analogs to discover the corresponding naphthalamideisoselenocyanate (NISC) and -selenourea (NSU) compounds, which led to the identification of dual topoisomerase 2 and the Akt pathway inhibitor activity of NISC-6 (16). In 2015, our group also demonstrated the leishmanicidal activity of selenocompounds (7), previously designed as antitumoral agents (17). In fact, selenium derivatives had been shown to reduce parasitemia and decrease clinical manifestations in infected mice (18).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…After 96 h, benzyl isocyanate gave compound 7 as a yellow powder. Yield: 43%; mp 213 to 215°C; IR ʋ max ( , N===-(Diselanediyldibenzene-4,1-diyl)bis[1-(4-methoxybenzyl) , N===-(Diselanediyldibenzene-4,1-diyl)bis[1-(n-butyl) , N===-(Diselanediyldibenzene-4,1-diyl)bis[1-(n-hexyl) 13 General procedure for the synthesis of thioureas 12 to 22. To a solution of diselenide (1.17 mmol) in dioxane (25 ml), the corresponding isothiocyanate (2.34 mmol, 1:2 molar ratio) was added and the mixture was kept at room temperature from 48 h to 144 h. The solvent was removed under vacuum by rotatory evaporation and the residue was treated with ethyl ether (50 ml) and washed with water (100 ml).…”
Section: Methodsmentioning
confidence: 99%
“…Our data revealed that some of these compounds possess potent activity with higher selectivity than the reference drugs miltefosine and edelfosine. Additionally, leishmanicidal activity in infected macrophages (THP-1 cells) was comparable to that of edelfosine (9)(10)(11)(12)(13)(14)(15)(16). Among the different selenium entities tested, 4,4=-diaminodiphenyldiselenide showed one of the most promising leishmanicidal activities.…”
mentioning
confidence: 90%